Parotid Duct Mucocele - Ong, C.A.; Prepageran, Narayanan; Loganathan, A.; Rahmat, Omar; Lingham, O.R. (Malaysian Medical Association, 2005)
Parotid swelling is a common presentation in ENT clinic. Most of the cases involve pathology of the gland. There are not many reported cases about parotid duct pathology. We describe a case of a large parotid duct mucocele with a calculus. Excision of the mucocele and superficial parotidectomy was performed. The post-operative recovery was uneventful.